2021
DOI: 10.1111/dme.14622
|View full text |Cite
|
Sign up to set email alerts
|

First‐line pharmacotherapy for incident type 2 diabetes: Prescription patterns, adherence and associated costs

Abstract: Aims To use real‐world prescription data from Alberta, Canada to: (a) describe the prescribing patterns for initial pharmacotherapy for those with newly diagnosed uncomplicated type 2 diabetes; (b) describe medication‐taking behaviours (adherence and persistence) in the first year after initiating pharmacotherapy; and (c) explore healthcare system costs associated with prescribing patterns. Methods We employed a retrospective cohort design using linked administrative datasets from 2012 to 2017 to define a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…Compliance, however, may be much lower than previously considered as a retrospective cohort study of 15,981 patients indicated 48% became nonadherent within the first year of treatment with metformin [29]. Discontinuance of metformin is primarily attributed either to side effects, or glycemic control being achieved independent of pharmacotherapy [29]. Similarly, a 2018 report indicated that 30% of prescribed doses of metformin were not taken, whereas higher adherence was seen for sulfonylureas, diphenyly-peptide-4 inhibitors (DPP-4 inhibitors, or gliptins) and sodium-glucose co-transport inhibitors-2 (SGLT-2, or gliflozins), but not for glucagon-like peptide-1 receptor agonists (GLP-1 receptor agonists) [29].…”
Section: Risk-benefits Of Chronic Metformin Usementioning
confidence: 82%
See 2 more Smart Citations
“…Compliance, however, may be much lower than previously considered as a retrospective cohort study of 15,981 patients indicated 48% became nonadherent within the first year of treatment with metformin [29]. Discontinuance of metformin is primarily attributed either to side effects, or glycemic control being achieved independent of pharmacotherapy [29]. Similarly, a 2018 report indicated that 30% of prescribed doses of metformin were not taken, whereas higher adherence was seen for sulfonylureas, diphenyly-peptide-4 inhibitors (DPP-4 inhibitors, or gliptins) and sodium-glucose co-transport inhibitors-2 (SGLT-2, or gliflozins), but not for glucagon-like peptide-1 receptor agonists (GLP-1 receptor agonists) [29].…”
Section: Risk-benefits Of Chronic Metformin Usementioning
confidence: 82%
“…The usual dose-range for metformin is from 250 to 2550 mg/day with plasma levels ranging from approximately 5 to 20 μM (Table 2). Compliance, however, may be much lower than previously considered as a retrospective cohort study of 15,981 patients indicated 48% became nonadherent within the first year of treatment with metformin [29]. Discontinuance of metformin is primarily attributed either to side effects, or glycemic control being achieved independent of pharmacotherapy [29].…”
Section: Risk-benefits Of Chronic Metformin Usementioning
confidence: 97%
See 1 more Smart Citation
“…35 This highlights the value of prioritizing shortages that pose the greatest risk to patients — an exercise operationalized in March 2020. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from PCOS are at risk of long-term negative health hazards that are not, or only partly addressed by the usual allopathic treatments, the adherence to which is suboptimal in real-world [33]. In addition, Metformin may induce Vitamin B12 deficiency [34].…”
Section: Discussionmentioning
confidence: 99%